The Effect of New Media Addiction: The Online Game Higgs Domino Island (Scatter) on Communications Students of 2018 Class of State Islamic University of North Sumatera (UINSU) - Miftahul Husna; Muhammad Alfikri (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The purpose of this article is to comprehend the impact of domino pencar island higgs in student of communication in class of 2018 of State Islamic University of North Sumatera (UINSU). At the moment, communication technology is entering a new medium through which social media can be advanced and easily accessible. This descriptive study makes use of qualitative data collection methods such as interviews, observation, and documentation. According to the findings of the study, three psychological symptoms predominate among college students: compulsive withdrawal symptoms, symptoms tolerance, and symptoms anxiety. These symptoms support the third argument that the new media has increased the failure rate of gambling sites. Filterisasi has blocked the government and will continue to limit social gambling and cognition students. Furthermore, damaged and a physical disturbance, as well as a psychological disorder, make students difficult.